Islamic philosophy, science, culture, and religion : studies in honor of Dimitri Gutas - Gutas, Dimitri.; Opwis, Felicitas Meta Maria.; Reisman, David. (Islamic Philosophy, Theology and Science. Texts and Studies, 2012)
Islamic intellectual thought is at the center of this collection of articles honoring Dimitri Gutas by friends, colleagues, and former students. The essays cover three main areas: the classical heritage and Islamic culture; classical Arabic science and philosophy; and Muslim traditional sciences. They show the interconnectedness between the Islamic intellectual tradition and its historical predecessors of Greek and Persian provenance, ranging from poetry to science and philosophy. Yet, at the same time, the authors demonstrate the independence of Muslim scholarship and the rich inner-Muslim debates that brought forth a flourishing scholastic culture in the sciences, philosophy, literature, and religious sciences. This collection also reflects the breadth of contemporary research on the intellectual traditions of Islamic civilization. Contributors include: Amos Bertolacci, Kevin van Bladel, Gideon Bohak, Sonja Brentjes, Charles Burnett, Hans Daiber, Gerhard Endress, William Fortenbaugh, Beatrice Gruendler, Jules Janssens, David King, Yahya Michot, Suleiman Mourad, Racha Omari, Felicitas Opwis, David Reisman, Heinrich von Staden, Tony Street, Hidemi Takahashi, Alexander Treiger, and Robert Wisnovsky.